Internet gaming disorder and suicidal behaviors mediated by sleep disturbance: a large-scale school-based study in 135,174 Chinese middle school students. - Peng, Pu; Chen, Zhangming; Ren, Silan; Liu, Yi; Li, Jinguang; Liao, Aijun; Zhao, Linlin; He, Ruini; Liang, Yudiao; Tan, Youguo; Tang, Jinsong; Chen, Xiaogang; et al. (European Child & Adolescent Psychiatry, 2025)
Emerging research suggests a positive association between Internet gaming disorder (IGD) and suicidal behaviors. However, existing studies predominantly focus on suicidal ideation rather than suicide attempts and often do not adequately control for potential psychological confounders. The mechanism linking IGD to suicidality remains unclear. This study aims to assess the independent association between IGD and suicidal behaviors and to examine the mediating role of sleep disturbance among Chinese adolescents. We recruited 135,174 middle school students from Zigong City using cluster sampling. Data on demographics, suicidal ideation, and suicidal attempts were collected. IGD was assessed using the Internet Gaming Disorder Scale-Short Form. Mental distress, including depression, anxiety, hyperactivity/inattention, conduct problems, sleep problems, and psychotic experiences, was evaluated using standardized questionnaires. Multiple logistic regression models and mediation analysis were conducted. The prevalence rates of IGD, suicidal behaviors, suicidal ideation, and suicide attempts were 1.6%, 16.7%, 11.9%, and 9.8%, respectively. Adolescents with IGD showed a significantly higher risk for suicidality: nearly 60% reported suicidal behaviors, 50% reported suicidal ideation, and 40% reported suicide attempts. Both IGD and gaming usage were independently linked to suicidal behaviors. Sleep disturbance partially mediated the relationship between IGD and suicidal behaviors, accounting for 47.0% of the total effect. Our studies call for timely and regular assessments for suicidality and sleep disturbance in IGD. Targeted interventions addressing sleep disturbance might reduce suicidal risk among adolescents with IGD.